Analisis Proses Pelaksanaan Pembelajaran Keterampilan Tata Boga Membuat “Kue Pastry” bagi Warga Belajar Paket C Kelas XI IPS di SPNF SKB Kota Samarinda - Atikah Maulidah (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2020)
In general, the learning process is only related to academic learning. However, it is different from culinary skills which are generally only implemented if there is training or activities that lead to specific training. However, in SPNF SKB Samarinda City implements culinary skills as learning is routinely carried out even into the curriculum so that it has a Learning Implementation Plan (RPP). The purpose of this study was to determine the implementation of learning culinary skills to make a "Pastry Cake" for Residents Learning Package C Class XI IPS at SPNF SKB Samarinda City. This type of research is a Qualitative Research in which the focus of research is Learning Catering Skills Making "Pastry Cake". This research was conducted at the SPNF SKB Samarinda City with 7 personnel as the subject of research including the head of the institution, 2 tutors, and 4 learning residents. Data collection techniques using interviews as the main method and observation and documentation as a support. Data analysis techniques include data collection, data simplification, data presentation, and drawing conclusions. The results showed: in the implementation phase in the learning activities of culinary skills using the 2013 curriculum, using group practice methods and carried out on Sundays starting at 09.00 am to finish. From the results of the above research it can be concluded that the process of implementing culinary skills learning to make "pastry cakes" for residents learning package c class XI IPS at SPNF SKB Samarinda City must meet all stages of the implementation in order to be well implemented. Citizens learn also to get the skills they can get.